A review of the physiological and histological effects of laser osteotomy - Rajitha Gunaratne, G.; Khan, R.; Fick, D.; Robertson, B.; Dahotre, N.; Ironside, Charlie (Taylor Francis Ltd, 2017)
Osteotomy is the surgical cutting of bone. Some obstacles to laser osteotomy have been melting, carbonisation and subsequent delayed healing. New cooled scanning techniques have resulted in effective bone cuts without the strong thermal side effects, which were observed by inappropriate irradiation techniques with continuous wave and long pulsed lasers. With these new techniques, osteotomy gaps histologically healed with new bone formation without any noticeable or minimum thermal damage. No significant cellular differences in bone healing between laser and mechanical osteotomies were noticed. Some studies even suggest that the healing rate may be enhanced following laser osteotomy compared to conventional mechanical osteotomy. Additional research is necessary to evaluate different laser types with appropriate laser setting variables to increase ablation rates, with control of depth, change in bone type and damage to adjacent soft tissue. Laser osteotomy has the potential to become incorporated into the armamentarium of bone surgery.